From CsPbBr(3) Nano-Inks to Sintered CsPbBr(3)–CsPb(2)Br(5) Films via Thermal Annealing: Implications on Optoelectronic Properties - Palazon, Francisco (J Phys Chem C Nanomater Interfaces, 2017)
[Image: see text] CsPbBr(3) nanocrystals passivated with short molecular ligands and deposited on a substrate were annealed from room temperature to 400 °C in inert atmosphere. Chemical, structural, and morphological transformations were monitored in situ and ex situ by different techniques, while optoelectronic properties of the film were also assessed. Annealing at 100 °C resulted in a 1 order of magnitude increase in photocurrent and photoresponse as a result of partial sintering of the NCs and residual solvent evaporation. Beyond 150 °C the original orthorhombic NCs were partially transformed into tetragonal CsPb(2)Br(5) crystals, due to the desorption of weakly bound propionic acid ligands. The photocurrent increased moderately until 300 °C although the photoresponse became slower as a result of the formation of surface trap states. Eventually, annealing beyond 350 °C removed the strongly bound butylamine ligands and reversed the transition to the original orthorhombic phase, with a loss of photocurrent due to the numerous defects induced by the stripping of the passivating butylamine.